EFL Teachers’ Attitude Towards Accent of Effective ELF Communication - Nurul Noviana (Universitas Negeri Makassar, 2020)
Over the years, English is best intended to be taught by a native speaker. Ironically, both native speakers and non-native speakers need to enhance their efficiency. As a qualified instructor of English, the habit of using accent preferences may affect interaction. This methodological research, therefore, examines the extent to which the ELF reference is rendered in the EFL classroom. By categorizing the open-ended question as to the first survey and continue to gather in-depth interviews, the perspectives on ideological preferences on particular accents were identified. As a result, the findings suggest that accents are not significant, preferably the usage of language between interlocutors to communicate has been proposed further.